(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
Uzbekistan’s relations with Kazakhstan, mutual exchanges, historical and cultural dialogues, mutual agreements and treaties were covered and analyzed based on sources. Uzbekistan’s mutual cooperation with Kazakhstan in the social, cultural, scientific, and educational spheres was touched upon. On the basis of mutual agreements, achievements were achieved in the social, cultural, scientific, and educational spheres.